Methodological Rigour and Transparency of Clinical Practice Guidelines Developed by Neurology Professional Societies in Croatia - Tudor, Katarina Ivana (Public Library of Science, 2013)
BACKGROUND: Clinical practice guidelines are systematically created documents that summarize knowledge and assist in delivering high-quality medicine by identifying evidence that supports best clinical care. They are produced not only by international professional groups but also by local professionals to address locally-relevant clinical practice. We evaluated the methodological rigour and transparency of guideline development in neurology formulated by professionals in a local medical community. METHODS: We analyzed clinical guidelines in neurology publicly available at the web-site of the Physicians’ Assembly in Croatia in 2012: 6 guidelines developed by Croatian authors and 1 adapted from the European Federation of Neurological Societies. The quality was assessed by 2 independent evaluators using the AGREE II instrument. We also conducted a search of the Cochrane Library to identify potential changes in recommendation from Cochrane systematic reviews included in guideline preparation. RESULTS: The methodological quality of the guidelines greatly varied across different domains. „Scope and Purpose” and „Clarity of Presentation“ domains received high scores (100% [95% confidence interval (CI) 98.5–100] and 97% [77.9–100], respectively), the lowest scores were in “Stakeholder Involvement“ (19% [15.5–34.6]) and “Editorial Independence” (0% [0–19.2]). Conclusions of 3 guidelines based on Cochrane systematic reviews were confirmed in updated versions and one update provided new information on the effectiveness of another antidepressant. Two Cochrane reviews used in guidelines were withdrawn and split into new reviews and their findings are now considered to be out of date. CONCLUSION: Neurological guidelines used in Croatia differ in structure and their methodological quality. We recommend to national societies and professional groups to develop a more systematic and rigorous approach to the development of the guidelines, timely inclusion of best evidences and an effort to involve target users and patients in the guideline development procedures.